2013
DOI: 10.11118/actaun201361010147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-sowing treatment and sowing season on Douglas fir emergence rate in a specific seed lot

Abstract: MARTINÍK ANTONÍN, PALÁTOVÁ EVA, HOUŠKOVÁ KATEŘINA: Impact of pre-sowing treatment and sowing season on Douglas fi r emergence rate in a specifi c seed lot. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 1, pp. 147-155 Not only in the Czech Republic there is a problem with low yield of Douglas fi r seedlings in forest tree nurseries. It can be caused mainly by two factors: the type of pre-sowing treatment and the temperature at the time of sowing. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
5
0
1
Order By: Relevance
“…These relatively short periods of higher temperatures apparently initiate the germination of seeds and their emergence. By contrast, low temperatures at early sowings may extend the process of cold stratification (Martiník et al 2013;Houšková et al 2014). This suggests that rather than by average temperature, the emergence rate of the tested seed lot is affected by the daily course of temperatures including maximal and minimal values.…”
Section: Discussionmentioning
confidence: 99%
“…These relatively short periods of higher temperatures apparently initiate the germination of seeds and their emergence. By contrast, low temperatures at early sowings may extend the process of cold stratification (Martiník et al 2013;Houšková et al 2014). This suggests that rather than by average temperature, the emergence rate of the tested seed lot is affected by the daily course of temperatures including maximal and minimal values.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses (Martiník et al 2013(Martiník et al , 2014a suggested that the option of 21 days of cold stratification of seeds (ISTA 2014, ČSN 48 1211:2006 recommended and applied in the field does not make full use of the seed potential. Although most of the filled seeds emerge during the growing season, the emergence rate is lower than that of seeds with extended stratification period.…”
Section: Discussionmentioning
confidence: 99%
“…One serious problem connected with artificial regeneration of this species is low yield of seedlings. Although there are more critical steps in nursery practice, in the case of Douglas fir, proper pre-sowing treatment, and also early microclimatic conditions are considered as the prevailing factors affecting the yield of seedlings (Heit, 1968;Martiník & Palátová, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…below 15 °C) will greatly reduce the germination capacity (Gosling, 1988;Bewley & Black, 1982). The extent of this dormancy depends on the provenance of Douglas fir seeds (Gosling & Peace, 1990;Dirr & Heuser, 2006;Martiník & Palátová, 2012).…”
Section: Introductionmentioning
confidence: 99%